The Political Economy of Policy Instrument Choice: Theory and Evidence from Agricultural Policies - Johan F. M. Swinnen; Alessandro Olper; Thijs Vandemoortele (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
We study the political economy of instrument choice in agricultural and food policies. After a review of the historical evolution of European agricultural price and trade policy instruments since 1880, we develop a political economy model of instrument choice. The key predictions of the model suggest a rational explanation of instrument choice patterns, based on the trade-off between the different cost components of the policies, and internal and external political constraints. An empirical analysis supports the main predictions of the theoretical model. We find that the GATT/WTO agreement had a significant impact.
Keywords: D78; Q18; 330; Political Economy; Instrument Choice; Agricultural Policy; GATT; WTO